Density‐ and trait‐mediated top–down effects modify bottom–up control of a highly endemic tropical aquatic food web. Issue 5 (2nd October 2012) - Dalton, C. M.; Mokiao‐Lee, A.; Sakihara, T. S.; Weber, M. G.; Roco, C. A.; Han, Z.; Dudley, B.; MacKenzie, R. A.; Hairston, N. G.
<x xml:space="preserve">Abstract</x> Benthic invertebrates mediate bottom–up and top–down influences in aquatic food webs, and changes in the abundance or traits of invertebrates can alter the strength of top–down effects. Studies assessing the role of invertebrate abundance and behavior as controls on food web structure are rare at the whole ecosystem scale. Here we use a comparative approach to investigate bottom–up and top–down influences on whole anchialine pond ecosystems in coastal Hawai'i. In these ponds, a single species of endemic atyid shrimp (Halocaridina rubra) is believed to structure epilithon communities. Many Hawaiian anchialine ponds and their endemic fauna, however, have been greatly altered by bottom–up (increased nutrient enrichment) and top–down (introduced fish predators) disturbances from human development. We present the results of a survey of dissolved nutrient concentrations, epilithon biomass and composition, and H. rubra abundance and behavior in anchialine ponds with and without invasive predatory fish along a nutrient concentration gradient on the North Kona coast of Hawai'i. We use linear models to assess 1) the effects of nutrient loading and fish introductions on pond food web structure and 2) the role of shrimp density and behavior in effecting that change. We find evidence for bottom–up food web control, in that nutrients were associated with increased epilithon biomass, autotrophy and nutrient content as well as increased abundance and size of H. rubra. We also find evidence for top–down control, as ponds with invasive predatory fish had higher epilithon biomass, productivity, and nutrient content. Top–down effects were transmitted by both altered H. rubra abundance, which changed the biomass of epilithon, and H. rubra behavior, which changed the composition of the epilithon. Our study extends experimental findings on bottom–up and top–down control to the whole ecosystem scale and finds evidence for qualitatively different effects of trait‐ and density‐mediated change in top–down influences.